(untitled) (Journal of the College of Basic Education, 2022)
The TV medium derives its current form in the dramatic raging process from the technological development taking place in all areas of artistic production production, all of which meet creatively in the umbrella of the TV picture, which mainly consists of basic rules and traditional systems from which this medium originated, but today, systems and New processes are closer to the technologies manufactured from them to methods and technical visions transformed the TV mediator from the ranks of previous classic operations into a new form and body for production and employment that made him leave all of the above, and he became trying to provide what is new and innovative in the field of technical treatments and jaw In the dramatic work, so this research studies a new innovative system in the field of dramatic TV production, which is the electronic image and the levels of its technical use in the medium TV show.